Idolatry and the artist's role with special reference to the work and thought of Andy Warhol - Waterkeyn, Linda Catherine (Rhodes University, Faculty of Humanities, Department of Fine Art, 1997)
This thesis uses Hirsch's dual notion of intention, i. e. conscious, intentional meaning and symptomatic, unconscious meaning, in order to avoid a dead end in the critical assessment of Warhol's work. T.S. Eliot's term "objective correlative" refers to a phenomenon whereby "an inner emotional reality" is evoked by its "external equivalent". (Benet, 1965). Thus, given that no work of art is purely self-referential (as distinct from its being autonomous),Hirsch's notion allows that viewerreconstruction of a painting involves shared values and concerns; that a painting reconstructed by a viewer acquires the status of an icon through which the viewer participates in the artist's sacred cosmos. Sociology of art tends on the whole to extrapolate from actual works to the alleged conditions that gave rise to them. That it cannot predict what specific works will arise from given conditions makes it unscientific. However, its usefulness lies in its ability to reveal what values and concerns are shared by artist and viewer. This is vital for an interpretation of Warhol's work. Warhol's biography leads directly into the meaning of his work. The sickly child of an immigrant steelworker, he grew up in Pittsburgh - an epitome of the technocratic-industrial environment - and was exposed from an early age to a violent and ugly world where the disparity between the super-wealthy and the struggling workers was deeply disturbing. That Warhol himself became a multi-millionaire artistic tycoon is significant, for it means that his works, his icons, were participatory in the very cultural myths and neuroses they appear to display or even despise. That his work has meaning and is open to interpretation there is no doubt. For example, a man-made soup can, as a manifestation and containment of the sacred, is coercive. Here the sacred becomes familiar, affordable and disposable. An electric chair, a man-made instrument of death, gives man supremacy over mortality and the divine prerogative of purging the world of all evil. The essay, however, does not attempt to answer the broader questions raised by Fromm and Roszak about the spiritual emptiness of the twentieth century and the existential crises experienced by those who hunger for meaning and fasten greedily onto anything that seems to proffer a glimpse of something beyond. The essay, nevertheless, strives within this context to elucidate the valid in Warhol's work
Keywords: Warhol, Andy, 1928-1987 -- Criticism and interpretation